2022
DOI: 10.25026/jtpc.v6i2.516
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic and Antioxidant Activities of Binahong [Anredera cordifolia (Ten.) Steenis] Leaf Ethanol Extract and Its Nanoemulsion Preparation in Swiss Webster Mice

Abstract: Platelet aggregation has the potential to form thrombi and result in cardiovascular system diseases such as myocardial infarction and ischemic stroke - one of the leading causes of death globally. Traditionally, people use binahong leaves as blood thinners. Therefore, this study aims to obtain scientific data on the efficacy of binahong leaf  as antithrombotic. The efficacy test was carried out on male Swiss-Webster mice. The results showed that the ethanol extract of binahong leaves at doses of 50 (BLEE50) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Binahong extract significantly inhibits lipid peroxidation in plasma and the liver and the formation of free radicals (p<0.01). Additionally, Binahong extract significantly reduces the average platelet volume (6.05 ± 0.24 fL vs. 6.55 ± 0.34 fL) and platelet distribution width (8.52±0.36% vs. 9.25±0.42%), suggesting that Binahong extract has potential as an antiplatelet and antioxidant agent [43]. Phytochemical analysis has revealed that Binahong possesses antioxidant activity, high levels of vitamin C, and phenolic components that inhibit the growth of both Gram-positive and Gram-negative bacteria, making it useful in the treatment of infectious diseases.…”
Section: Binahong For Internal Diseasesmentioning
confidence: 92%
“…Binahong extract significantly inhibits lipid peroxidation in plasma and the liver and the formation of free radicals (p<0.01). Additionally, Binahong extract significantly reduces the average platelet volume (6.05 ± 0.24 fL vs. 6.55 ± 0.34 fL) and platelet distribution width (8.52±0.36% vs. 9.25±0.42%), suggesting that Binahong extract has potential as an antiplatelet and antioxidant agent [43]. Phytochemical analysis has revealed that Binahong possesses antioxidant activity, high levels of vitamin C, and phenolic components that inhibit the growth of both Gram-positive and Gram-negative bacteria, making it useful in the treatment of infectious diseases.…”
Section: Binahong For Internal Diseasesmentioning
confidence: 92%